2009
DOI: 10.1049/el.2009.1007
|View full text |Cite
|
Sign up to set email alerts
|

P and B doped Si resonant interband tunnel diodes with as-grown negative differential resistance

Abstract: Robust Si resonant interband tunnel diodes have been designed and tested that demonstrate as-grown negative differential resistance at room temperature with peak-to-valley current ratios (PVCR) up to 2.5 and peak current densities in the order of 1 kA/cm 2 . The as-grown Si p þ in þ structures were synthesised using solid source molecular beam epitaxy, incorporating B and P d-doped layers. Both structures have shown thermal stability after 1 min post-growth anneals up through 6758C and the PVCR improves to 2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Postgrowth annealing was determined to be unnecessary for CVD-grown RITDs, unlike their MBE grown counterparts, due to the higher growth temperatures employed resulting in fewer vacancy defects [21]. It is recognized that some reports of MBE-grown RITDs without postgrowth annealing have been disclosed [14], [18], but annealing always improves an MBE grown diode, regardless of its as-grown performance. All measurements presented have been performed on 18-μm dots and were performed on pieces from the center of the 200-mm wafers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postgrowth annealing was determined to be unnecessary for CVD-grown RITDs, unlike their MBE grown counterparts, due to the higher growth temperatures employed resulting in fewer vacancy defects [21]. It is recognized that some reports of MBE-grown RITDs without postgrowth annealing have been disclosed [14], [18], but annealing always improves an MBE grown diode, regardless of its as-grown performance. All measurements presented have been performed on 18-μm dots and were performed on pieces from the center of the 200-mm wafers.…”
Section: Resultsmentioning
confidence: 99%
“…A pure Si RITD, avoiding the complexity of Ge incorporation, resulted in a PVCR of 2.05 [17]. More recently, a Si-only RITD with a PVCR of 2.48 and J p of 1.5 kA/cm 2 , without requiring postgrowth anneal, has been reported [18]. Current densities can be tuned with the RITD for specific applications by varying the tunneling barrier thickness, resulting in seven orders of magnitude variation of current densities from 218 to 20 mA/cm 2 for barrier thicknesses ranging from 2.5 to 16 nm [19], [20].…”
Section: Epitaxy (Mbe) At 370mentioning
confidence: 99%
“…Past Si/SiGe RITD device results using the LT-MBE technique have shown that although postgrowth annealing may not be necessary to achieve room-temperature NDR, in all cases reported to date, the PVCR always increased with annealing [15]- [19], although a recent report demonstrated PVCR in excess of two for as-grown RITDs [19].…”
Section: Methodsmentioning
confidence: 94%
“…It has been also reported a RITD with a cutoff frequency of 20GHz, allowing for the first time, applications of mixed signal, RF and high speed logic circuits [6] . Simpler and compatible with CMOS process to fabricate Tunneling Diodes have been recently reported: structures that do not need Ge [7] , and a fabrication process based on CVD (Chemical Vapor Deposition) instead of MBE [8] (Molecular Beam Epitaxy) is presented. Another explored option is the development of procedures for III-V RTDs compatible with silicon substrates.…”
Section: Introductionmentioning
confidence: 99%